Antibiotic use and ileocolonic immune cells in patients receiving fecal microbiota transplantation for refractory intestinal GvHD: a prospective cohort study. (December 2021) - Spindelboeck, Walter; Halwachs, Bettina; Bayer, Nadine; Huber-Krassnitzer, Bianca; Schulz, Eduard; Uhl, Barbara; Gaksch, Lukas; Hatzl, Stefan; Bachmayr, Victoria; Kleissl, Lisa; Kump, Patrizia; Deutsch, Alexander; et al.
Introduction: Treatment-refractory, acute graft- versus -host disease (GvHD) of the lower gastrointestinal tract (GI) after allogeneic hematopoietic stem cell transplantation is life threatening and lacks effective treatment options. While fecal microbiota transplantation (FMT) was shown to ameliorate GI-GvHD, its mechanisms of action and the factors influencing the treatment response in humans remain unclear. The objective of this study is to assess response to FMT treatment, factors influencing response, and to study the mucosal immune cell composition in treatment-refractory GI-GvHD. Methods: Consecutive patients with treatment-refractory GI-GvHD were treated with up to six endoscopically applied FMTs. Results: We observed the response to FMT in four out of nine patients with severe, treatment refractory GI-GvHD, associated with a significant survival benefit ( p  = 0.017). The concomitant use of broad-spectrum antibiotics was the main factor associated with FMT failure ( p  = 0.048). In addition, antibiotic administration hindered the establishment of donor microbiota after FMT. Unlike in non-responders, the microbiota characteristics (e.g. α- and β-diversity, abundance of anaerobe butyrate-producers) in responders were more significantly similar to those of FMT donors. During active refractory GI-GvHD, an increased infiltrate of T cells, mainly Th17 and CD8 + T cells, was observed in the ileocolonic mucosa of patients, while the number of immunomodulatory cells such as regulatory T-cells and type 3 innate lymphoid cells decreased. After FMT, a change in immune cell patterns was induced, depending on the clinical response. Conclusion: This study increases the knowledge about the crucial effects of antibiotics in patients given FMT for treatment refractory GI-GvHD and defines the characteristic alterations of ileocolonic mucosal immune cells in this setting.